EFEKTIVITAS PROGRAM PENANGANAN DAN PENCEGAHAN TINDAK KEKERASAN TERHADAP ANAK DI KABUPATEN WONOGIRI - Pebriyanti, Pebriyanti; Lituhayu, Dyah; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This research aims to determine the effectiveness of the program for handling and preventing acts of violence against children in Wonogiri Regency, as well as analyzing the factors that hinder the effectiveness of the program for handling and preventing acts of violence against children. This research use desciptive qualitative approach. Data collection techniques through interviews, observation and documentation. The research results show that the program for handling and preventing acts of violence against children in Wonogiri Regency is not fully effective. This can be seen from the goal which cannot be said to have been achieved because there are still cases of violence. Then we still encounter obstacles such as employees who are less committed to carrying out their duties, lacking facilities and infrastructure, and community culture that is difficult to change.